Neonatal ethanol exposure from ethanol-based hand sanitisers in isolettes. Issue 1 (6th June 2017) - Hsieh, Shizuka; Sapkota, Amir; Wood, Rebecca; Bearer, Cynthia; Kapoor, Shiv
Abstract : Objective: The aims of this study is to measure the ethanol vapours in the isolette after use of hands cleaned with ethanol-based hand sanitiser (EBHS). Methods: Two squirts (1.5 mL) of hand sanitiser were rubbed on hands for 10 or 20 s before inserting the hands in the isolette for 5 min. Ethanol vapours were measured in the isolette with photoionisation detector and alcohol breathalyser for 30 min. Results: Peak ethanol concentration in the isolette was considerably higher with a 10 s hand rub (381±192 ppm) compared with a 20 s hand rub (99±50 ppm), and dissipated to ≤5 ppm within 30 min. Under routine care, EBHS use by care providers exposes neonates in isolettes to 3.7–7.3 or 1.4–2.8 mg/kg ethanol per day with 10 or 20 s hand rubs, respectively. The expected blood level from average single exposure is 0.036 mg/dL with 10 s hand rub and may increase further with multiple exposures in a short period. Conclusion: Preterm neonates in the isolette are at risk of inadvertent exposure to ethanol. The expected blood alcohol level from this exposure is small and below 1 mg/dL level recommended by European Medicines Agency to limit the ethanol exposure in children. The unintended ethanol exposure can be avoided by rubbing hands for at least 20 s after applying EBHS.